(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Khanal N, Panthi S, Pandey MP, Luitel H, Poudel RR, Bhusal N. 2024. Deciphering genetic variation of terminal heat stress-responsive traits in Nepalese wheat germplasm using phenotyping and functional marker analysis. Asian J Agric 8: 134-141. Development of heat-tolerant wheat cultivars is becoming more essential for the food security due to the increasing impact of global warming. In the present study, Nepalese bread wheat accessions, along with the check varieties were evaluated under late-sown heat stress conditions, followed by genotyping of selected accessions using trait-based functional markers. The findings showed a reduction in Thousand-Grain Weight (TGW), Grain Weight per Spike (GWS), and Grain Filling Duration (GFD), due to the late-sown heat-stressed environment. The reduction for GFD and GWS among the wheat accessions ranged from 22.2 to 62.3% over the heat-tolerant check genotypes (NL-971 and Aditya), respectively. The correlation and principal component analysis showed that TGW, GWS, and GFD were positively associated with each other. The analysis of functional markers CWI21 and CWI22 (linked to TaCwi-A1 and TaCwi-A2 genes) and GS7D (linked to TaGS-D1a or TaGS-D1b genes) showed an association with the TGW. The accessions NGRC-02584 and NGRC-02602 possessed the positive alleles of markers CWI22 and GS7D for a higher TGW, indicating that these accessions have the potential to withstand terminal heat stress and could be included in breeding programs after validation.